AFM and electrochemical studies of mono- and bis-anthracene derivatives of C-60 deposited on gold electrodes - Rendon, M; Hyde, M; Suarez, M; Duarte-Ruiz, A; Compton, R (2005)
Four different anthracene substituted C60 species, specifically:9′,10′-dihydro[9′,10]-ethaneanthracene[11′, 12′:1,2]-[5,6]-fullerene C60,di{9′,10′- dihydro[9′,10]-ethaneanthracene[11′,12′:1,2;11″, 12″:18,36]}-[5,6]-fullerene C60,di{9′,10′- dihydro[9′,10]-ethaneanthracene[11′,12′:1,2;11″, 12″:30,58]}-[5,6]-fullerene C60,di{9′,10′- dihydro[9′,10]-ethaneanthracene[11′,12′:1,2;11″, 12″:56,60]}-[5,6]-fullerene C60,are deposited by the evaporation of toluene solutions on to gold electrodes. They are characterized using electrochemical methods and atomic force microscopy (AFM). It is shown that they display generic behavioural similarities to C60, but also exhibit important differences. These include differing deposit morphologies and differing solubilities of the species' ions formed via electroreduction in acetonitrile. Film re-distribution resulting from reductive dissolution followed by immediate re-oxidation is also examined. © 2005 Elsevier B.V. All rights reserved.